Is there a win for conservation, livelihoods and governance? : the implications of Broussonetia papyrifera as an ecological resource substitute: a field study in Uganda - Stoderegger, Yasmin (SLU/Dept. of Urban and Rural Development, 2018)
Wood extraction and invasive species are commonly perceived as harmful for ecosystem services and detrimental for conservation efforts. However, they can also be beneficial for forests as well as for local communities. Interactions among economic, institutional and ecological factors may in some cases turn these impacts on their head. Here, I present a case study of a location where this may be the case. Villages often depend on nearby forests for natural resources, as is the case around Mabira Central Forest Reserve in Eastern Uganda, where such needs are intensified by the lack of other income-generating opportunities. The demand for forest products such as charcoal and firewood is high due to population pressure and the cost of other energy sources. The park is managed by the Ugandan National Forestry Authority (NFA) and faces pressures from within the reserve and from external actors. It is also beset by a lack of functioning governance structures. This demand for wood products is to a high degree met by Broussonetia papyrifera, an invasive exotic tree introduced in the 70s. As a fast-growing species, it supports multiple uses that may spare slower-growing native species from being harvested. It has also shown positive effects on soil fertility. This study compares previous biodiversity data from these sites with current forest measurements and data gathered through social science methods including semi-structured interviews, key informant interviews and focus group discussions in two communities adjacent to the forest reserve. Results show that although still controversial for conservation efforts, Broussonetia papyrifera can support the regeneration of indigenous species and as such increase species richness and at least maintains biodiversity. The results also show that Broussonetia papyrifera has a crucial role for local livelihoods as it supplies various provisioning services such as fodder for livestock, fuelwood for energy, medicinal use, raw material for timber and poles and regulating services such as a soil fertilizer and stabilizer. It also has medicinal uses that are not explored yet. In a country like Uganda where there is a lack of strong institutions, implementing forest protection policies, Broussonetia papyrifera acts as a resource substitute with the potential to help avoid further degradation deeper in the reserve and to support local livelihoods.